2012
DOI: 10.1007/s00248-012-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial Consortia and Previous Exposure Enhance the Biodegradation of Sulfonamides from Pig Manure

Abstract: Persistence or degradation of synthetic antibiotics in soil is crucial in assessing their environmental risks. Microbial catabolic activity in a sandy loamy soil with pig manure using 12C- and 14C-labelled sulfamethazine (SMZ) respirometry showed that SMZ was not readily degradable. But after 100 days, degradation in sulfadiazine-exposed manure was 9.2%, far greater than soil and organic manure (0.5% and 0.11%, respectively, p < 0.05). Abiotic degradation was not detected suggesting microbial catabolism as mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(25 citation statements)
references
References 69 publications
4
21
0
Order By: Relevance
“…Finally, also for the group Brevundimonas spp. some literature data exist proving that these organisms might play a role in the removal of antibiotics [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, also for the group Brevundimonas spp. some literature data exist proving that these organisms might play a role in the removal of antibiotics [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Islas-Espinoza et al (2012) observed an increase in species richness as determined by Shannon-Wiener and Margalef indexes in a soil supplemented with sulfamethazine. Shade et al (2013), using a 16S rRNA gene sequencing approach, compared soil bacterial communities under apple trees (Malus domestica) that had undergone spray treatments with streptomycin sulphate.…”
Section: Introductionmentioning
confidence: 92%
“…This has been previously undertaken using Density Gradient Gel Electrophoresis (DGGE) (Jechalke et al, 2014;Kopmann et al, 2013;Reichel et al, 2013;Westergaard et al, 2001), or Terminal Restriction Fragment Length Polymorphism (T-RFLP) (Islas-Espinoza et al, 2012) analysis of fragments of the 16S rRNA gene. Westergaard et al (2001) demonstrated a decrease in diversity (as indicated by reduced banding complexity resolved by DGGE) in soils treated with tylosin as well as an increased abundance of some taxa, the identity of which were not determined.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamide adapted bacterial cultures however, were able to degrade sulfonamides very rapidly (0.2 to 3 days) (Ingerslev and Halling-Sørensen, 2000). The accelerating effect of previous exposure was also shown in a study in pig manure (Islas-Espinoza, 2012). It has been suggested that little or no biodegradation occurs whenever there are other easily biodegradable sources of carbon and nitrogen present (Drillia, 2005), which is obviously the case in manure and manure amended soils.…”
Section: Sulfonamidesmentioning
confidence: 87%